2022
DOI: 10.58629/mjms.v30i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Checklists of crustaceans of freshwater and marine fishes of Basrah Province, Iraq

Abstract: Reviewing the literature on all the crustaceans parasitizing freshwater and marine fishes of Basrah province, Iraq indicated the presence of 74 crustacean taxa. Sixty-five taxa belonged to the class Maxillopoda while nine taxa belonged to the class Malacostraca. All these crustaceans were adults living on the external surface of their fish hosts while three taxa were reported as larvae. Fifty-five species of such crustaceans were recorded from marine localities, 11 from freshwater localities and the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…With this article and the previous allied articles (Mhaisen et al, 2013a, b, c;Ali et al, 2014;Mhaisen et al, 2014;Khamees et al, 2015), checklists of all the groups of protozoan and metazoan parasites infecting fishes of Basrah Province were achieved. However, it is appropriate to mention here that Al-Maliki et al (2015) indicated that a protozoan cyst was recovered from the intestine of Coptodon zillii (reported as Tilapia zillii) from Tigris River, north of Qurna City.…”
Section: Addendamentioning
confidence: 94%
See 1 more Smart Citation
“…With this article and the previous allied articles (Mhaisen et al, 2013a, b, c;Ali et al, 2014;Mhaisen et al, 2014;Khamees et al, 2015), checklists of all the groups of protozoan and metazoan parasites infecting fishes of Basrah Province were achieved. However, it is appropriate to mention here that Al-Maliki et al (2015) indicated that a protozoan cyst was recovered from the intestine of Coptodon zillii (reported as Tilapia zillii) from Tigris River, north of Qurna City.…”
Section: Addendamentioning
confidence: 94%
“…For these reasons, it was decided to review these data; revise names of both parasites and fishes in accordance with updated references and electronic sites and to provide an updated fish-parasite checklist in addition to the protozoan and myxozoan lists. This review is a continuation of series of literature reviews on major groups of parasites of fishes in Basrah Province of Iraq (Mhaisen et al, 1993;2013a, b, c;Ali et al, 2014;Mhaisen et al, 2014;Khamees et al, 2015). Finally, it was also planned to compare the richness of infected fishes of this province with protozoans and myxozoans with those of the whole country of Iraq based on data extracted from the indexcatalogue of parasites and disease agents of fishes of Iraq (Mhaisen, 2016).…”
Section: Introductionmentioning
confidence: 99%